Efficacy of Facilitated Capacity Building in Providing Cleft Lip and Palate Care in Low- and Middle-Income Countries. Issue 7 (October 2017) - Jenny, Hillary E.; Massenburg, Benjamin B.; Saluja, Saurabh; Meara, John G.; Shrime, Mark G.; Alonso, Nivaldo
Abstract : Abstract: Providing surgical repair for congenital anomalies such as cleft lip and palate (CLP) can be challenging in low- and middle-income countries. One nonprofit organization seeks to address this need through a partnership model. This model provides long-term aid on multiple levels: surgeon and healthcare provider education, community outreach, and funding. The authors examined the effectiveness of this partnership model in providing CLP care and increasing cleft care capacity over time. This organization maintains data on each partner and procedure and collected data on hospital and patient characteristics through voluntary partner surveys from 2010 to 2014. Effectiveness of care provision outcomes included number of surgeries/partner hospital and patient demographics. Cleft surgical system strengthening was measured by the complexity of repair, waitlist length, and patient follow-up. From 2001 to 2014, the number of procedures/hospital/year grew from 15 to 109, and frequency of alveolar bone grafts increased from 1% to 3.4%. In addition, 97.9% of partners reported that half to most patients come from rural areas. Waitlists decreased, with 9.2% of partners reporting a waitlist of ≥50 in 2011 versus 2.7% in 2014 ( P < 0.001). Patient follow-up also improved: 35% of partners in 2011 estimated a follow-up rate of ≥75%, compared with 51% of partners in 2014 ( P < 0.001). The increased number of procedures/hospital/year supports the partnership model's effectiveness in providing CLP care. In addition, data supports cleft surgical system strengthening—more repairs use alveolar bone grafts, waitlists decreased, and follow-up improved. These findings demonstrate that the partnership model may be effective in providing cleft care and increasing cleft surgical capacity.